Charging plasma microparticles by electron and ion fluxes with kappa distribution in collisional mode - Myrzaly, М.; Masheyeva, R.U.; Jumagulov, М.N. (Recent Contributions to Physics, 2024)
This work investigates the current problem of charging dust particles in nonequilibrium plasma, taking into account the kappa distribution of particles. Equations are obtained to describe the charging of dust particles based on the kappa distribution, taking into account collisions of plasma particles leading to ion charging. The transition from a thin collisionless region li(e)  a is considered with the assumption that li(e)
Keywords: charging of dust particles; particle fluxes; collision mode; nonequilibrium plasma